Humanitarian intervention and conflict resolution in West Africa from ECOMOG to ECOMIL - Kabia, John M. (Ashgate Pub., 2009)
By using the empirical case of ECOWAS, this book examines the challenges posed by complex political emergencies (CPEs) to humanitarian intervention. It traces the evolution of ECOWAS from an economic integration project to that of a security organisation and examines the challenges inherent in such a transition.